Heterologous, Expression, and Characterization of Thermostable Glucoamylase Derived from Aspergillus flavus NSH9 in Pichia pastoris - Kazi Muhammad, Rezaul Karim; Ahmad, Husaini; Md. Anowar, Hossain; Ngieng, Ngui Sing; Fazia, Mohd Sinang; Mohd Hasnain, Md Hussain; Hairul Azman, Roslan (Hindawi Publishing Corporation, 2016)
A novel thermostable glucoamylase cDNA without starch binding domain (SBD) of Aspergillus flavus NSH9 was successfully identified, isolated, and overexpressed in Pichia pastoris GS115.The complete open reading frame of glucoamylase from Aspergillus flavus NSH9 was identified by employing PCR that encodes 493 amino acids lacking in the SBD. The first 17 amino acids were presumed to be a signal peptide.The cDNA was cloned into Pichia pastoris and the highest expression of recombinant glucoamylase (rGA) was observed after 8 days of incubation period with 1% methanol. The molecular weight of the purified rGA was about 78 kDa and exhibited optimum catalytic activity at pH 5.0 and temperature of 70∘C. The enzyme was stable at higher temperature with 50% of residual activity observed after 20 min at 90∘C and 100∘C. Low concentration of metal (Mg++, Fe++, Zn++, Cu++, and Pb++) had positive effect on rGA activity.This rGA has the potential for use and application in the saccharification steps, due to its thermostability, in the starch processing industries.